Using choice experiments to value a world cultural heritage site : reflections on the experimental design - Gomes, Lina Lourenço (2013)
In the context of public amenities, whose benefits of preservation are not totally reflected by the market, the valuation of cultural heritage has given primacy to the contingent valuation method, with very few attempts being made to valuation via the discrete choice experiments technique (DCE). In the present paper, from among the various phases of the DCE conception, particular emphasis is given to the way in which the attributes levels are combined into alternatives and how they are allocated into choice sets (experimental design step). In order to configure hypothetical scenarios relating to the conservation of a World Heritage cultural landscape, this paper applies both the experimental design strategies identified in the literature review as commonly applied in DCE to value cultural items, as well as D-optimal processes, which proved to be advantageous both in terms of statistical efficiency and in the information required (number of choice sets).